Firefighters under alert: psychological morbidity, empathy and alexithymia between firefighters and non-firefighters - Rodrigues, Fabiana (2023)
Firefighters have high exposure to traumatic events and have an increased risk of developing symptoms related to trauma. The current study assessed the psychological morbidity, empathy and alexithymia of volunteer firefighters compared to career firefighters and to non-firefighter comparators from the general population. Group differences were assessed using multivariate comparisons and univariate tests and discriminant analysis for individual measures. A total of 1062 individuals completed the protocol. Considering firefighters as the focus of analysis, data suggested that both career and volunteer firefighters presented higher trauma than the comparison group. In subscales of empathy, compared to the comparison group, career firefighters scored higher on the perspective-taking scale, while firefighters showed less personal discomfort and less fantasy. Firefighters showed less alexithymia, in the outward-oriented style of thinking than the comparison group. The findings suggest the need for more prevention and treatment efforts for firefighters, with the introduction of educational and therapeutic interventions.